Effectiveness of commercial forestry policy in contributing to the promotion of sustainable household income in Northern Uganda - Uwonda, Gilbert; Bedijo, Geoffrey (Global Advanced Research Journal of Management and Business Studies, 2013)
This study aimed at examining the effectiveness of commercial forestry policy in contributing to the promotion of sustainable household income and analyzing the factors that affect implementation of the current Commercial Forestry Policy in Northern Uganda. Although Commercial Forestry Policy and supportive laws exist for the development of commercial forestry, which together with other socioeconomic activities, mainly agriculture, could improve socio-economic conditions of households in this area with vast arable land, the population has remained largely poor with most of the land unutilized. A cross-sectional survey design was used. Questionnaires and key informant interviews were employed to collect data from opinion leaders at the local community level, local government leaders and personnel, private tree farmers, National Forestry Authority staff, Non Governmental Organizations' staff involved in forestry activities and forest produce entrepreneurs. The data was analyzed by measuring the frequencies of occurrence of sets of responses and Pearson’s correlation analysis The findings revealed that commercial forestry is effective in contributing to the promotion of sustainable household income but there has been, inadequate public awareness, lack of seeds/planting stocks and funds The study recommended that continuous awareness creation be conducted and assistance in terms of inputs be extended to this community to encourage commercial forestry and improve household income